O atual plano nacional de educação - Shirlei de Souza Corrêa; Aline Leandra Coelho (Doxa, 2018)
This paper constitutes a documentary analysis aimed at understanding how the curriculum policies for Basic Education are dealt with in the National Education Plan - PNE (2014-2024), sanctioned by Law 13,005 of 06/25/2014. The PNE presents ten guidelines, twenty goals and two hundred and fifty-four strategies with the aim of improving the quality of education, universalizing school attendance, promoting democratic management and valuing education professionals. The operationalization of this document takes place through public policies developed in the form of Programs and other actions in a collaboration regime of the Union, States, Federal District and Municipalities. Although we recognize the importance of this document for the Brazilian educational context, we realized with the analysis that the curricular issues are not a priority in this document, because they are secondary to the access and permanence of students in the different stages of Basic Education.